Development of the Sandro Application (Statistics on Android) as a Learning Media in the Educational Statistics - Pratama, Apriliyanus Rakhmadi; Masenge, Anugerah Daeng; Yasin, Moh Fahri (Akademika : Jurnal Teknologi Pendidikan, 2024)
This study focuses on the development of an Android-based learning application to enhance student interest and understanding in the course of Educational Statistics at IAIN Sultan Amai Gorontalo. Using a research and development (R&D) approach, the study includes the stages of needs analysis, application design, material development, implementation, and evaluation. The evaluation results from subject matter experts show that the presented material aligns with curriculum standards and learning needs. Media experts’ validation indicates that the application has an attractive and functional interface, although some improvements are required to enhance the practicality and efficiency of the application. User trials (students) yielded positive responses, with an average score of 81,17%, indicating that most users found the application effective in supporting the Educational Statistics course. This application development significantly contributes to creating relevant and engaging learning media, providing a solution to the low student interest in this course.